Devakoshthas (niches) containing deities on the Mandapa - Temples of India Project Team (Jio Institute, 2024)
The northern side lateral transept attached to the mandapa (pillared hall) of the Mahanleshwar Temple has devakoshthas (niches) on all sides containing deities. Seen here is probably a broken sculpture of a river goddess in one of the niches flanked by a row of pilaster motifs and dancing figures. The dwarf wall of the transept has kakshasana (seat backs) containing designs of balustrades separating the sculptural depictions formed in circles.